2015
DOI: 10.3109/03091902.2015.1016190
|View full text |Cite
|
Sign up to set email alerts
|

Reliability assessment for pulse wave measurement using artificial pulse generator

Abstract: This study aimed to assess intrinsic reliabilities of devices for pulse wave measurement (PWM). An artificial pulse generator system was constructed to create a periodic pulse wave. The stability of the periodic output was tested by the DP103 pressure transducer. The pulse generator system was then used to evaluate the TD01C system. Test-re-test and inter-device reliability assessments were conducted on the TD01C system. First, 11 harmonic components of the pulse wave were calculated using Fourier series analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…One is the coefficient of variation of harmonic amplitude among pulses within one measurement (WCV \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$_{\mathrm {cn}})$ \end{document} . Since the WCV \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$_{\mathrm {cn}}\text{s}$ \end{document} were less than 3% using TD01C in the phantom study [43] , the WCV \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$_{\mathrm {cn}}\text{s}$ \end{document} beyond 3% revealed that the variation were partially introduced by the arterial system of the subject. The previous reports had shown that this within-measurement variation of the harmonics reflected the stage of severity in dying patients [56] , [57] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is the coefficient of variation of harmonic amplitude among pulses within one measurement (WCV \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$_{\mathrm {cn}})$ \end{document} . Since the WCV \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$_{\mathrm {cn}}\text{s}$ \end{document} were less than 3% using TD01C in the phantom study [43] , the WCV \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$_{\mathrm {cn}}\text{s}$ \end{document} beyond 3% revealed that the variation were partially introduced by the arterial system of the subject. The previous reports had shown that this within-measurement variation of the harmonics reflected the stage of severity in dying patients [56] , [57] .…”
Section: Discussionmentioning
confidence: 99%
“…TD01C should operate within working condition: \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$0\sim 2.5$ \end{document} PSI (peak to peak pressure), 23°C-35°C, and 15% to 85% Relative humidity. The instrument reliability of TD01C had been validated before the measurements were performed [43] .…”
Section: Methodsmentioning
confidence: 99%
“…All subjects underwent radial pulse wave measurements and recorded C4CV values at baseline. Radial pulse waves were noninvasively measured by medical‐grade devices that had been found to be highly reproducible (Chang and Wang ), and the intra‐observer and inter‐observer reliabilities met the criteria for medical interpretation (Portney and Watkins ; Chang et al ). The standard operating procedures for environmental temperature control and radial pressure wave measurement were as described in previous studies (Chang et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…Each subject was asked to lie down in a supine position and rest for 5 minutes before the measurement. The pulse pressure was then recorded on the left-hand radial artery with a pulse wave analyzer TD01C (MII-ANN Technology, Taiwan), which has proven its intrinsic reliability using the artificial pulse generator [27] . The intra-observer and inter-observer reliabilities of TD01C were also demonstrated in the clinical study [28] .…”
Section: Methodsmentioning
confidence: 99%